Inulin alleviates atherosclerosis through improving lipid metabolism, inflammation, and gut microbiota in ApoE-knockout mice: the short-chain is more efficacious - Zhang, Kun; Zeng, Yu; Li, Jiawei; Huang, Yingchun; Zhang, Nan; Gong, Yue; Xiao, Kaihu; Chen, Jian; Chen, Tiantian; Qiu, Haomin; Lei, Sisi; Yan, Fei; et al. (Frontiers in Pharmacology, 2024)
Introduction Atherosclerosis (AS) is considered the underlying cause of many diseases, particularly cardiovascular and cerebrovascular diseases. Inulin, a type of fructan, has shown potential in improving atherosclerosis, although there are conflicting findings. It is hypothesized that the polymerization degree of inulin may largely influence its therapeutic effectiveness. Therefore, this study aimed to investigate the effects and mechanisms of short-chain and long-chain inulin in AS. Methods ApoE−/− mice fed a high fat diet (HFD) were used to establish an atherosclerosis model. These mice received daily oral administration of either short-chain or long-chain inulin for 12 weeks. Plasma lipid metabolism-related indices were measured using biochemical analysis, and plasma immunological indices were analyzed via ELISA. The aorta, aortic root regions, liver tissue, adipose tissue, and colon tissue were examined through various staining techniques, including ORO staining, hematoxylin and eosin staining, Alcian blue staining, and immunofluorescent or immunohistochemical assays. Microbiome analysis was conducted in the cecal content. Results The results indicated that both short-chain and long-chain inulin substantially reduced the formation of atherosclerotic plaques. Inulin also improved plasma lipid concentrations and hepatic lipid metabolism, and partially alleviated both localized (atherosclerotic lesions) and systemic inflammation. Short-chain inulin was more effective than long-chain inulin in reducing atherosclerotic plaques formation, enhancing lipid metabolism and reducing inflammation. Additionally, both types of inulin showed similar effectiveness in enhancing intestinal epithelial barrier integrity, gut microbiota composition and functionality. Conclusion These findings suggest that inulin has a protective role against atherosclerosis by enhancing lipid metabolism, reducing inflammation, and improving intestinal barrier and gut microbiota. As a dietary intervention, short-chain inulin is more effective than long-chain inulin, offering clinical implications for using inulin as a therapeutic agent for atherosclerosis.